(untitled) (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the effect of the 4H strategy on the achievement of female students in the second intermediate year in physics through the following hypothesis: There is no statistically significant difference at the level of significance (0.05) between the average grades of the female students in the experimental group that will be taught according to the 4H strategy and the average grades of the control group that will study the same subject according to the traditional method of achievement. The research is limited to the female students of the second intermediate grade in Al-Shams Girls’ Middle School affiliated with the General Directorate of Education of Baghdad/AAl-Karkh II for the academic year 2023-2024. The first three chapters of the physics book for the second intermediate grade were included, and two classes were randomly selected out of six classes, representing the experimental group and the control group. The research sample was distributed as follows: 32 female students for the experimental group and 32 female students for the control group. The achievement test consists of 40 items. The process necessitated twelve weeks, with two sessions for each group. The results showed that the experimental group outperformed the control group in the achievement test. Based on these research results, the researchers presented several recommendations and suggestions